Designing the city of the future: comprehensive and gender-inclusive strategies for sustainable urban mobility in the Buenos Aires Metropolitan Area - Mendiola, Lorea; González, Pilar (Frontiers in Sustainable Cities, 2025)
IntroductionThis study analyzed gender disparities in daily mobility patterns in the Buenos Aires Metropolitan Area, with a focus on the impacts of built environment factors and considering the socioeconomic characteristics of the individuals.MethodsUsing data from the 2018 Household Mobility Survey and multilevel regression models, the gender gap in mobility was analyzed with a particular emphasis on work commutes and accompanying trips. The inclusion in the analysis of gender interactions, in particular with transportation and land use factors, is a novel contribution to the field, as it allowed us to analyze in depth the extent to which these factors differentially affect the urban mobility of men and women and could, therefore, contribute to widening or narrowing the gender mobility gap.Results and discussionOur findings demonstrated that public transport availability and land-use characteristics primarily affect travel time and distance, with gender-differentiated impacts. Women benefited more from improved public transport coverage and diversity, while higher population density, greater self-containment, and higher density of street intersections reduced travel distances and travel times in general, although they affected women’s mobility less. This study underscores the need of integrating gender perspectives into sustainable urban mobility strategies to ensure equitable access to goods and services. However, urban and transport policies alone would be insufficient to reduce the mobility gap, because the results showed that individual socioeconomic characteristics also significantly influence mobility, with women facing greater constraints due to domestic responsibilities or limited access to private vehicles. A comprehensive approach incorporating social measures addressed to mitigate the restrictions that women face is essential to achieving a gender-inclusive mobility.